A new Clymenura (Polychaeta: Maldanidae) from the intertidal of Banks Peninsula, New Zealand, with a reassessment of Leiochone Grube, 1868 and Clymenura Verrill, 1900 - Read, Geoffrey B. (Zootaxa, 2011)
A maldanid discovered on sand beaches of Banks Peninsula, South Island, New Zealand is newly described. Clymenura snaiko sp. nov. is of large size at over 250 mm length, with 18 chaetigers, two achaetous preanal segments with tori, unmodified dentate uncini in anterior chaetigers, a ventral glandular shield on chaetiger eight, a high cephalic rim notched laterally, and a deep anal funnel rimmed with 16 short subequal cirri and one longer ventral cirrus. The confused taxonomy of ventral-shield-bearing maldanids is reassessed and clarified. Leiochone Grube 1868 and Clymenura Verrill, 1900 are here treated as the valid members of Arwidsson’s (1906) tribe Leiochonini in Euclymeninae, and given emended diagnoses, while Imajima and Shiraki’s (1982) subfamily Clymenurinae and Clymenura subgenus Cly. (Cephalata) are considered invalid. Differentiating character states of the valid Leiochonini species are tabulated. Leiochone is restricted to six species, including the new combinations L. annulata (Mohammad, 1980) and L. japonica (Imajima & Shiraki, 1982). Clymenura is restricted to nine valid taxa, including Cly. snaiko sp. nov. and the new combination Cly. polaris lena (Averincev, 1990). These updated groupings exclude a further eight nominal taxa which mostly may be indeterminable. Leiochone species occur in inshore temperate to tropical Eastern Hemisphere waters, while Clymenura mostly occur in high North European latitudes and the northern Pacific region, usually offshore in deep water. The new species is the first record of a Clymenura from Southern Hemisphere waters, and the second member of the genus to be found in the intertidal.